Halofuginone attenuates osteoarthritis by inhibition of TGF-β activity and H-type vessel formation in subchondral bone. Issue 9 (15th October 2015) - Cui, Zhuang; Crane, Janet; Xie, Hui; Jin, Xin; Zhen, Gehua; Li, Changjun; Xie, Liang; Wang, Long; Bian, Qin; Qiu, Tao; Wan, Mei; Xie, Min; et al.
Abstract : Objectives: Examine whether osteoarthritis (OA) progression can be delayed by halofuginone in anterior cruciate ligament transection (ACLT) rodent models. Methods: 3-month-old male C57BL/6J (wild type; WT) mice and Lewis rats were randomised to sham-operated, ACLT-operated, treated with vehicle, or ACLT-operated, treated with halofuginone. Articular cartilage degeneration was graded using the Osteoarthritis Research Society International (OARSI)-modified Mankin criteria. Immunostaining, flow cytometry, RT-PCR and western blot analyses were conducted to detect relative protein and RNA expression. Bone micro CT (μCT) and CT-based microangiography were quantitated to detect alterations of microarchitecture and vasculature in tibial subchondral bone. Results: Halofuginone attenuated articular cartilage degeneration and subchondral bone deterioration, resulting in substantially lower OARSI scores. Specifically, we found that proteoglycan loss and calcification of articular cartilage were significantly decreased in halofuginone-treated ACLT rodents compared with vehicle-treated ACLT controls. Halofuginone reduced collagen X (Col X), matrix metalloproteinase-13 and A disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS 5) and increased lubricin, collagen II and aggrecan. In parallel, halofuginone-attenuated uncoupled subchondral bone remodelling as defined by reduced subchondral bone tissue volume, lower trabecular pattern factor (Tb.pf) and increased thickness of subchondral bone plate compared with vehicle-treated ACLT controls. We found that halofuginone exerted protective effects in part by suppressing Th17-induced osteoclastic bone resorption, inhibiting Smad2/3-dependent TGF-β signalling to restore coupled bone remodelling and attenuating excessive angiogenesis in subchondral bone. Conclusions: Halofuginone attenuates OA progression by inhibition of subchondral bone TGF-β activity and aberrant angiogenesis as a potential preventive therapy for OA.